A Novel Panel of 43 Insertion/Deletion Loci for Human Identifications of Forensic Degraded DNA Samples: Development and Validation - Jin, Rui; Cui, Wei; Fang, Yating; Jin, Xiaoye; Wang, Hongdan; Lan, Qiong; Guo, Yuxin; Chen, Chong; Zhang, Xingru; Zhu, Bofeng (Frontiers in Genetics, 2021)
Insertion/deletion polymorphism is a promising genetic marker in the forensic genetics, especially in the forensic application of degraded sample at crime scene. In this research, a novel five-dye multiplex amplification panel containing 43 highly polymorphic InDel loci and one Amelogenin gene locus is designed and constructed in-house for the individual identification in East Asian populations. The amplicon sizes of 43 InDel loci are less than 200bp, which help to ensure that full allele profiles can be obtained with degraded DNA sample. A series of optimizations and developmental validations including optimization of PCR conditions, detection efficiency of the degraded and casework samples, sensitivity, reproducibility, precision, tolerance for inhibitors, species specificity and DNA mixtures are performed following the SWGDAM guidelines. The results of the internal validations demonstrated that this novel InDel panel was a reliable, sensitive and accurate system with different tolerances to different inhibitors, and performed a considerable detection efficiency for the degraded or mixed samples, which could be used in the forensic applications.